2013
DOI: 10.1021/la404153t
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Pull Off of Nanoparticles Adhering to Compliant Substrates

Abstract: It is widely known in adhesive contact mechanics that a spherical particle will not detach from an elastic half-space unless a critical level of pulling force is reached, as already revealed by JKR- or DMT-type deterministic models. This article focuses on the scenario of particle-substrate adhesion where the size of particles is down to the nanometer scale. A consequence of particle size reduction to this range is that the energy scale confining the state of system equilibrium becomes comparable to the unit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For example, by treating the separation process as a thermally activated escape from an energy well [95], the average time for the forced detachment, between a nanosized spherical particle and a soft substrate in adhesive contact (Figure 10a), to take place is shown in Figure 10b. Evidently, in direct contrast to that from deterministic considerations, detachment can occur even if the pulling force is well below the critical pull-off level.…”
Section: Non-specific Adhesion On Wavy/rough Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, by treating the separation process as a thermally activated escape from an energy well [95], the average time for the forced detachment, between a nanosized spherical particle and a soft substrate in adhesive contact (Figure 10a), to take place is shown in Figure 10b. Evidently, in direct contrast to that from deterministic considerations, detachment can occur even if the pulling force is well below the critical pull-off level.…”
Section: Non-specific Adhesion On Wavy/rough Surfacesmentioning
confidence: 99%
“…Corresponding predictions from the deterministic Maugis model [94] are also shown by dashed lines (modified with permission from [95]). …”
Section: Modeling Specific Adhesionmentioning
confidence: 99%
“…when adhesion has been completely disrupted before axotomy). However, for adherent axons, our observations clearly showed that beading sites may co-localize with strong adhesion regions, indicting the role of cell adhesion [34,4851] in the initial growth/nucleation of beads. This heterogeneous effect could also arise from the internal structure of the axon where discontinuous gaps between the ends of microtubules as well as their connection with the cytoskeleton and membrane may exist, which can certainly play a role in bead formation [31,32].…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…Lin and coworkers 29 have developed a model for the force required to remove a nanoparticle from a substrate. Similarly, mean-field theory has been used to measure how confinement effects the interactions between assemblies of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%